2018
DOI: 10.1523/eneuro.0303-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

LOTUS Inhibits Neuronal Apoptosis and Promotes Tract Regeneration in Contusive Spinal Cord Injury Model Mice

Abstract: Nogo receptor-1 (NgR1) signaling is involved in the limitation of axonal regeneration following spinal cord injury (SCI) through collapsing the growth cone and inhibiting neurite outgrowth. Lateral olfactory tract usher substance (LOTUS), a NgR antagonist, suppresses these pathological conditions. A previous report demonstrated the positive effects of LOTUS expression on motor function through raphespinal tract regeneration using pan-neuronally LOTUS-overexpressing transgenic mice. However, this report used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Protein isolation and Western blotting assay were performed as described previously . Detailed methods are presented in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Protein isolation and Western blotting assay were performed as described previously . Detailed methods are presented in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…We generated an SCI animal model by inducing contusive SCI with moderate severity at the 10th thoracic vertebrae level in adult female immunodeficient mice. 14,30,58 5.0 × 10 5 ffiPSC-gNS/PCs were transplanted into the center of the lesion 9 days after the SCI. First, to investigate any configuration changes of the injured spinal cord, we examined the cross-sectional area of the injured spinal cord by H&E staining 12 weeks after transplantation ( Figure S3A).…”
Section: Transplanted Ffipsc-gns/pcs Survive Migrate and Differenmentioning
confidence: 99%
“…Neuronal apoptosis is an important component of secondary SCI and spinal nerve cell death after SCI is caused by apoptosis . Studies in different SCI models have confirmed that neuronal apoptosis is widespread in secondary SCI . Apoptosis, also known as programmed cell death, is an intrinsic natural physiological process that maintains the stability of various tissues in the human body by eliminating metabolites of dead cells .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Studies in different SCI models have confirmed that neuronal apoptosis is widespread in secondary SCI. 6,7 Apoptosis, also known as programmed cell death, is an intrinsic natural physiological process that maintains the stability of various tissues in the human body by eliminating metabolites of dead cells. 7 The mechanism of apoptosis in nerve cells is very complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation